Spatial Integration in the Fishermen Settlement of Sungai Pinang Nagari, Pesisir Selatan Regency - Windri Hadi Utama; Al Busyra Fuadi; Era Triana (International Journal Labs, 2026)
Regional development has introduced land access through a main road, leading to shifts in settlement orientation and the spatial configuration of Sungai Pinang Nagari, a fishing village in Pesisir Selatan Regency. Previously oriented toward water as the primary access, the spatial layout along the riverbanks now faces the risk of degradation due to these changes. Therefore, a study is needed to plan the spatial integration of existing areas. This research employed a mixed-method approach, combining qualitative rationalistic methods to holistically understand local spatial values and quantitative methods based on the Space Syntax concept—specifically, integrity analysis—to identify spaces with high integration value. These highly integrated spaces function as connectors and integrators, linking and harmonizing with other spatial zones. The findings reveal three high-integrity spaces: Integrity Space A along the coastal zone, Integrity Space B in the communal zone, and Integrity Space C along the riverbank zone. These spaces form integrative areas known as “grey spaces,” which support and connect various community activities. This study concludes that despite the shift toward a land-based orientation, spaces rooted in local wisdom retain significant potential as integrative and connective elements within a sustainable spatial framework.